Arterial calcification and long-term outcome in chronic limb-threatening ischemia patients. Issue 132 (November 2020) - Konijn, Louise C.D.; Takx, Richard A.P.; de Jong, Pim A.; Spreen, Marlon I.; Veger, Hugo T.C.; Mali, Willem P.Th.M.; van Overhagen, Hendrik
Highlights: Annularity of peripheral arterial calcification is a predictor for survival in CLI. The predictive value is higher than the traditional prognostic risk factors of CLI. Severity, thickness and continuity of arterial calcification was not predictive. Annularity of calcifications may improve prognostic modelling for CLI patients. Detecting annular calcifications on CT can distinguish potential CLI patients at risk. Abstract: Purpose: Within five years after presentation 50–60% of patients with chronic limb-threatening ischemia (CLI) have died or had an amputation. We assessed the predictive value of lower extremity arterial calcification on computed tomography (CT) characteristics on both 7-years amputation-free survival and 10-years all-cause mortality in patients with CLI. Method: Included were 89 CLI patients (mean age 73.1 ± 11.6 years) who underwent a CT angiography of the lower extremities. In the femoropopliteal and crural arteries based on a CT score the following calcification characteristics were assessed: severity, annularity, thickness and continuity. The predictive value of different arterial calcification characteristics was analysed by age- and sex-adjusted multivariate Cox regression analysis. Results: Complete annular calcifications were common (femoropopliteal 43.7%, n  = 38; crural, 63.2%, n  = 55). Mean survival was 278.4 weeks (95% CI 238.77–318.0 weeks). Patients with complete annular calcifications had a higher all-cause 10-year mortality (femoropopliteal unadjusted HR 1.64, p  = 0.04 and adjusted for age and sex HR 1.68, p  = 0.04; crural unadjusted HR 1.92, p  = 0.02, adjusted for age and sex HR 2.29, p  = 0.006) than patients with other calcification characteristics. Conclusions: Annularity of calcification of both femoropopliteal and crural arteries is a predictor for 10-year all-cause survival, its hazard being even higher than the traditional prognostic risk factors for CLI and therefore could be involved in the poor survival of these patients.